The evaluation of the Standing Committee on Public Accounts' oversight role and purpose in promoting accountability :a case of the Limpopo Provincial Legislature - Makgwathana, Pheyaa Alfred (My University, 2023)
This study explored the underlying problem of financial mismanagement in the public sector with pertinence to public accountability in South Africa. The problem of accountability has manifested in growing wasteful, irregular, and fruitless expenditure in the post-apartheid era, which is confronted by other multitude of social-economic challenges. Post-1994, South Africa embarked on an effort of policy development and legislative reforms to cater to public service regulation. These include legislative frameworks such as the 1999 Public Finance Management Act and the 2003 Municipal Finance Management Act. To date, South Africa is still struggling with measures to counter corruption and the abuse of state resources. Given that South Africa has instituted and inaugurated several critical institutional mechanisms for legislative oversight, the study sought to explore the rationale for rampant problems pertaining to non-compliance, unaccountability, and lack of answerability within South Africa’s public sector. This calls for research since these problems have serious implications for the future of the country and its ability to address inequalities relating to the history of exclusion of most people, especially Africans. Due to a rise in irregular and wasteful expenditure, this study highlighted the roles and functions of SCOPA as a key parliamentary tool for advancing accountability. The research objectives for the study were grounded on the growing problem of financial misconduct and abuse of public funds in the public sector due to lack of accountability, despite the existence of SCOPA as a parliamentary oversight mechanism. From the reviewed literature, the Limpopo Provincial Legislature faces several challenges such as a lack of accountability, specifically on executives’ accountability on their actions. Also, several departments attest to having several irregularities, fruitless and wasteful expenditures that affect service delivery, otherwise, the need for SCOPA to intervene. However, the SCOPA resolutions are not effectively implemented by the Limpopo Provincial Department and its municipalities. It is on this basis that the current study sought to evaluate SCOPA’s oversight role and purpose in promoting accountability in the Limpopo Provincial Legislature. The study adopted theory triangulation as the theoretical approach for the study, this is evident through the utilisation of four theories, which includes, Principle-agent theory (Mithick;1970); Functionalism theory (Parsons, 1930s); Constitutionalism theory (Locke;1680s) and Institutionalism theory (Meyer & Rowan, 1970s). These theories were adopted as the theoretical points of departure for the study due to their richness in examining issues of oversight and accountability. To explore the study, a triangulation research approach (qualitative & quantitative) was adopted. The data was collected from SCOPA members and members of the Limpopo Provincial Legislature. The collected data was analysed quantitatively and qualitatively for detailed findings. The study reveals that SCOPA is not operating effectively to oversee and monitor public expenditure. The oversights done by Limpopo Provincial Legislature did not address issues pertaining to public finance management, which speaks volume in terms of accountability. From the findings of the study, it is evident that Limpopo Provincial Legislature is still facing several challenges, which ultimately affect service delivery. Towards addressing the problem of oversight and accountability, most of the study’s respondents recommend that the system, process, procedures, and policies be reviewed, and SCOPA is required to establish new strategies that will help to fast-track the investigation within public institutions. Also, the provincial department is required to provide reviewed information within the agreed period. This study submits that provincial legislature should establishes other independent institutions to work in collaboration with SCOPA.
Thesis (Ph.D. (Administration)) -- University of Limpopo, 2023
Keywords: Accountability; Oversight; Standing Committee of Public Accounts; Democracy; Good governance; Public administration -- South Africa -- Limpopo; Corporate governance -- South Africa --Limpopo; Administrative remedies -- South Africa -- Limpopo